Use of 129caesium, 99Tcm stannous pyrophosphate, and a combination of the two in the assessment of myocardial infarction. Issue 8 (August 1978) - Walton, S; Kafetzakis, E; Shields, R A; Testa, H J; Rowlands, D J
Abstract : Acutely damaged myocardium was shown in 103 patients with suspected acute myocardial infarction using 99Tcm pyp. A significant incidence of false positive and false negative results occurred, 'true' results being defined by standard clinical, electrocardiographic, and enzyme criteria. Localisation of infarction compared reasonably well with standard electrocardiographic criteria but more frequently suggested true posterior involvement. Serial estimates of infarct size may be of value in the recognition of infarct extension during the acute phase. Viable perfused myocardium was shown in 63 patients with a variety of cardiac disorders using 129Cs. The technique gives a reliable indication of anterior infarction but tends to underestimate inferior infarction. There was good correlation with the electrocardiogram with regard to localisation and extent of infarction. Nineteen patients received both isotopes and were included in each of the above groups. The combination permits further assessment of equivocal results Furthermore as 129Cs demonstrates both previous and recent infarction and 99Tcm pyp accumulates only in acutely damaged myocardium it was possible to estimate the extent of previous and recent myocardial damage.